1989
DOI: 10.1007/bf00027545
|View full text |Cite
|
Sign up to set email alerts
|

Population analysis in mass cultures of Tubifex tubifex

Abstract: Mass cultures of Tubifex tubijkx from Lake Orta were kept in the lab at 20 'C starting with different initial densities (10, 45, 86, 161 ind *jar-'), with the aim of evaluating the effect of density on population numbers and on population parameters. The results show that density mainly controls fecundity, growth, maturation and ovigeration rates. Growth rates and mean number of eggs laid/ovigerous (R,) are inversely related to density, but generation time appears to be directly related. Very low or very high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Type B genotypes reached the highest weights and produced one cocoon per individual during a two week period whereas Type A needed 10 weeks. Hence, Type B produced a mean of 0.42 eggs per day and reached similar values of egg production as were described by Bonacina et al (1989), 0.33-0.51 eggs per day, 20 "C, but lower than that of Kosiorek (1974), 0.61 eggs/day, 24 "C, Wisniewski (1979), 0.4-0.9 eggs/day in the field, 5 ' C, and Finogenova 8c Lobasheva (1987), 2 eggs/day. Due to its higher weight and greater production of eggs one may assume that Type B is more efficient than Type A in gaining energy from the food.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Type B genotypes reached the highest weights and produced one cocoon per individual during a two week period whereas Type A needed 10 weeks. Hence, Type B produced a mean of 0.42 eggs per day and reached similar values of egg production as were described by Bonacina et al (1989), 0.33-0.51 eggs per day, 20 "C, but lower than that of Kosiorek (1974), 0.61 eggs/day, 24 "C, Wisniewski (1979), 0.4-0.9 eggs/day in the field, 5 ' C, and Finogenova 8c Lobasheva (1987), 2 eggs/day. Due to its higher weight and greater production of eggs one may assume that Type B is more efficient than Type A in gaining energy from the food.…”
Section: Discussionmentioning
confidence: 61%
“…Unfortunately, from the fresh weight data it is not clear that the genotypes have different growth rates. Reynoldson (1987) and Bonacina et al (1989) showed that worms reaching higher weights had a higher growth rate and that larger worms also produced more eggs. These results coincide with my data on production of cocoons and fresh weights which show that these differences are genotype dependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation